Implementation of Ideal Democracy in The General Election System in 2024 in Indonesia - Hani Mulyani (JURNAL HUKUM SEHASEN, 2023)
Some countries have adopted a parliamentary system and some have adopted a presidential system to build democracy. Meanwhile, Indonesia initially practiced democracy with a parliamentary system but was considered a failure, until finally Indonesia practiced democracy with a presidential system. The implementation of the parliamentary and presidential electoral systems is still being debated today, this is reinforced by the option to hold elections in 2024 with a closed proportional electoral system, which closed proportional system will return Indonesia to the New Order era which adheres to the parliamentary electoral system. The purpose of this study is to understand whether the presidential system is the ideal electoral system of government in the 2024 elections. The method in writing is to use the literature method and use analytical techniques to collect data from various data obtained. The result of this research is that the presidential system is the ideal electoral system for the upcoming 2024 elections, reinforced by reasons that argue that the parliamentary electoral system is not convincing for Indonesia now.